ANALISIS PENGARUH SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SUMBAWA BARAT - Dewi, Sinar Laksamana; Ismawati, I; Sumbawati, Novi Kadewi (Pusat Riset dan Publikasi, 2024)
This study aims to determine the effect of the tourism sector on the Locally-Generated Revenue (PAD) of West Sumbawa District. This type of research is associative which aims to analyze the influence of the tourism sector which is proxied by the number of tourist visits (X) on the Locally-Generated Revenue (PAD) of West Sumbawa District. The type of data used was quantitative data. This study used secondary data collected using documentation techniques obtained from documents published by the Central Statistics Agency (BPS) of West Sumbawa District. The collected of data was processed using statistical processing software Statistical Package for The Social Science (SPSS) to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and determinant coefficient testing (R2). The results of this study showed that tourist visits had a positive and significant effect on the Locally-Generated Revenue (PAD) of West Sumbawa District. This means that the more tourists who come to visit will increase the more Locally-Generated Revenue (PAD) of West Sumbawa District. Likewise, the decrease in the number of tourists who come to visit will decrease the more Locally-Generated Revenue (PAD) of West Sumbawa District. The ability of the tourist visit variable to effect on the Locally-Generated Revenue (PAD) of West Sumbawa District was 59.4%, while the remaining of 40.6% was effected by other variables outside this research model, such as the number of tourist attractions, the number of cultural attractions, the number of hotels, and the number of restaurants.